Training to strengthen the mental self-boundary (Self-Boundary Awareness Training, SBAT) results in greater mindfulness: How self-boundary awareness increases mindfulness - Blaser, Klaus; Buchli-Kammermann, Jacqueline (Advances in Social Sciences Research Journal, 2017)
Abstract 42 individuals completed an 8-week course to strengthen the mental self-boundary. The group met on seven evenings (2 ½ hours) and for an entire day (6 hours) to exchange experiences and train the conscious perception of their mental self-boundary in pairs or as a group. At home they carried out a guided imagination exercise every day and kept a diary on specific self-boundary issues. The participants also received theoretical input on the spatial Boundary-Based Awareness Model and had the opportunity to physically experience the various mental perspectives in relation to their own inner mental world and that of others. Participants did not carry out any specific mindfulness exercises at home. Evaluation of FMI and BPS questionnaires completed before and after the training revealed a greatly improved score for the self-boundary domain as well as a significant improvement in the mindfulness score. Below we describe the training in more detail and discuss how self-boundary training could lead to greater mindfulness.